Die anthropomorphen Terrakotten der Region am syrischen Mittleren Euphrat im 3. Jahrtausend v. Chr. - Ferhan Sakal (Les Carnets de l’ACoSt)
This volume provides a study on the 3rd millennium B.C. anthropomorphic clay figurines of the Middle Euphrates region. The research is based on over 2400 specimens, mostly in a fragmentary state, retrieved in thirteen different salvage excavations located along the Middle course of the Syrian Euphrates, from Tell Shiyukh Tahtani to the north to Tall Bi’a to the south.